Final report: numerical and physical models of urban heat islands - Meroney, Robert N., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1974)
The response in the atmosphere of stratified shear layers to nonhomogeneous surface features is the subject of this report. Many interesting atmospheric circulations such as the sea breeze, the urban heat island, and flow over a heated island in the ocean (heat mountain) are induced by unbalanced bouyancy forces as a result of differential surface temperature. Such phenomena are very complex since the motion is coupled with several dominant features such as thermal stratification, high roughness elements, nonuniformity of surface roughness and/or surface temperature, nonplanar boundaries, and unsteadiness of boundary conditions. These problems may be successfully examined, however, by a coordinated laboratory-analytical research effort. This report summarizes a numerical and experimental research program which examined such a complicated airflow over nonhomogeneous surface complexities in two- and three-dimensional space.
CER74-75RNM26.
Prepared by Robert N. Meroney, Principal Investigator.
NSF Grant, ENG-72-03938 (GK33800).
December 1974.
Keywords: Air -- Pollution; Urban pollution